El decomiso de bienes relacionados con el delito en la legislación penal peruana - García Cavero, Percy (2018)
This article deals with the figure of forfeiture of assets related to crime. The point of reference is Peruvian criminal legislation. Although the analysis focuses on the substantive norms, some procedural considerations are also made.